Simulation and Estimation of Hedonic Models - James J. Heckman (Center for Economic Studies and ifo Institute (CESifo), 2003)
Making use of restrictions imposed by equilibrium, theoretical progress has been made on the nonparametric and semiparametric estimation and identification of scalar additive hedonic models (Ekeland, Heckman, and Nesheim, 2002) and scalar nonadditive hedonic models (Heckman, Matzkin, and Nesheim, 2002). However, little is known about the practical aspects of estimating such models or of the characteristics of equilibrium in such models. This paper presents computational and analytical results that fill some of these gaps. We simulate and estimate examples of equilibrium in the additive hedonic models and provide evidence on the performance of several estimation techniques. We also simulate examples of equilibria in nonadditive models and provide evidence on the performance of the nonadditive estimation techniques developed in Heckman, Matzkin, and Nesheim (2002).
Keywords: 330; hedonic models; non-parametric methods; simulation; Monte Carlo; additive models; nonadditive models